PENGARUH MUTU PELAYANAN DAN KEPUASAN MAHASISWA TERHADAPKINERJAKARYAWAN PADA STMIK GLOBAL TANGERANG BANTEN - Wuly Sudarmi (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to determine the influence of Service Quality on employee performance, the influence of student satisfaction on employee performance, the influence of service quality and student satisfaction simultaneously on the performance of STMIK Global Tangerang Banten employees. This research was conducted from April to September 2018, with an explanatory type of research which was also correlational, with the survey method using a questionnaire where respondents were students of STMIK Global Tangerang Banten. the population of this study was 266 people, then through the Slovin formula set a sample of 160 respondents. Data analysis was carried out descriptively and test causal hypotheses. In Hypothesis Test through SPSS where hypothesis (1) Value of t = 13,865 is greater than table t of 1,65 and significant of 0,000 is smaller than 0,05, therefore H0 is rejected and H1 is accepted meaning Service Quality influences Employee Performance. Hypothesis (2) Value of t = 13,003 is greater than table t of 1,65 and significant of 0.000 is smaller than 0.05, therefore H0 is rejected and H1 is accepted meaning that student satisfaction affects Employee Performance . Hypothesis (3) Value of F = 96.778 is greater than table F of 3.94 and significant of 0.000 is smaller than 0.05, therefore H0 is rejected and H1 is accepted meaning that. Employee Performance simultaneously affects the Service Quality and Student Satisfaction.